The gut microbiota of pregnant and non-pregnant female Hipposideros pomona - Taif Shah; Yuting Ning; Jiuxuan Zhou; Qi Liu; Zahir Shah; Wenhua Zhao; Binghui Wang; Xueshan Xia (BMC Microbiology)
Abstract The Pomona roundleaf bats (Hipposideros pomona) have unique ecological and physiological adaptations to various habitats in South Asia, including China. Despite its ecological significance, the gut microbiota plays a key role in regulating host immunity and reproductive physiology, possibly connecting microbial dynamics to fertility outcomes. In this study, we used V3-V4 16 S rRNA high-throughput sequencing to elucidate the diverse microbiota structure of pregnant and non-pregnant female H. pomona in Yunnan, China. We found that pregnant female bats had a more diverse gut microbiota community, with a significant increase in the phyla Bacteroidetes and Alphaproteobacteria. Following a similar trend, the families Enterobacteriaceae and Streptococcaceae were more abundant in the guts of pregnant H. pomona than in non-pregnant ones, which contained more Nocardioidaceae and Peptostreptococcaceae. Pregnant H. pomona had more Lactococcus, Burkholderia, Salinisphaera, and Mycobacterium in their guts than non-pregnant ones, which had more Romboutsia, Clostridium, and Enterococcus, making the guts intriguing. PICRUSt2-based KEGG functional annotation revealed diverse microbiota functions associated with increased metabolic activity during pregnancy. Increased function annotations in the human disease categories were related to bacterial infectious diseases, parasitic infectious diseases, cancer, and cardiovascular diseases, indicating that microbiota during pregnancy becomes more stress-responsive and pathogenic. Our findings highlight the importance of monitoring wild bat-associated gut microbe alterations during reproductive status. Future research will focus on the gut microbiota’s role in reproductive success, as well as its pathogenic potential and impact on overall wildlife health.